Perception and awareness of preventive practices against breast cancer among women in Ibadan, Oyo State, Nigeria (2018)
The prevalence of breast cancer which is the second deadly disease in the world, has affected the peace of women as the vulnerable group in the society, thus has attracting more global and scholarly attention.While researches have focused largely on the symptoms and consequences of breast cancer among women, few have focused on women’s perception and awareness about the preventive practices of this disease especially in Oyo state. This forms the focus of this paper. Marxist feminist theory formed the framework of the study. A descriptive survey was conducted among 400 women selected from two local governments in Ibadan through multi stage sampling. Ten in-depth interviews were also conducted among women. Quantitative data was analyzed using inferential statistics such as percentages and chi-square, while the qualitative data were content analyzed. The study revealed that women’s perception of breast cancer was based on poor knowledge and the ‘belief’ that breast cancer is not only caused by supernatural forces but can be cured by it (God/gods) even without medical intervention. Eightythree (83) percent were aware of breast self-examination, 66% were aware of clinical breast examination and 28% of mammography. However, awareness about other preventive practices like exercise, avoidance of alcohol intake, weight loss and diet was low and awareness was significantly related to women’s level of education with X2=44.0, P = 0.00. There is need for awareness programs and health education on breast cancer to reduce the myth about breast cancer and encourage early detection and treatment of this deadly disease.